FAST AND ACCURATE EMD-CCA BASED METHOD TO REMOVE EYE BLINK ARTIFACTS FROM EEG - SOOMRO, MUMTAZ HUSSAIN (2014)
Electroencephalography (EEG) is non-invasive neuroimaging technique which is used to record the electrical potentials generated by human brain activity. The EEG is recorded through the electrodes placed on human scalp using 10-20 electrode placement system. It is very difficult to interpret the EEG recording when it is contaminated by noise originating from physiological activities such as; cardiac activity, muscle activity, eye blink and an eye movement activity; which are known as artifacts. But the most prominent artifact is the eye blink artifact, having amplitude of 10-100 times greater than the amplitude of cerebral activity which makes EEG data to have low signal-to-noise ratio (SNR). An increased amount of activity in eye blinks may severely impact the interpretation of the EEG. Several techniques have been proposed by the different authors to remove eye blink artifacts from the EEG.